Corporate Social Responsibility and Financial Performance on Going Concern - Diyah Santi Hariyani (Hut Publication Business and Management, 2023)
The Covid-19 pandemic has not ended until now. The majority of companies experienced a decline in performance. The objectives of this study are identify the effect of Corporate Social Responsibility (CSR) and financial performance ongoing concerns in industrial and chemical manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2020. A quantitative method using purposive sampling techniques. Sample data used are secondary data with the documentation method. Data secondary data with documentation methods. Data downloaded from the www.idx.co.id, in the form of financial statements. The data analysis method used is classical assumption test multiple and linear regression analysis with SPSS version 25 software. This study indicates that Corporate Social Responsibility has a significance level of 0.003 and financial performance has a significant level of 0.028 with a significance level of 0. ,05. It concluded that the results of this study indicate that Corporate Social Responsibility and financial performance have a positive and significant effect on the going concern company.